Efficient routing protocol for scatternet bluetooth mobility model / Nur Solehah Rasali - Rasali, Nur Solehah (2015)
Scatternet Bluetooth ad hoc network is an infrastructureless where the nodes forming the temporary network without wired or need for base station. Due to its link instability, the node mobility and the routing topologies frequently changing it becomes one of main issues need to be concerned. This project analyse performance of node mobility models over scatternet Bluetooth routing protocol based throughput, packet delivery fraction, dropped packet, and end-to-end delay by increasing number of nodes density and number of node mobility pause time. Then, determine the suitable node mobility model such as Random WayPoint (RWP), Random Direction Model (RDM), and random Walk Model (RWM) for Ad-hoc On-Demand Distance Vector (AODV), Dynamic Source Routing (DSR), Destination Sequenced Distance Vector (DSDV) Bluetooth routing protocol. In order to determine its performance simulation needs to be done. BonnMotion has been used to create a node mobility model and UCBT (stands for University of Cincinnati-Bluetooth) has been chosen on NS-2 simulator as their ability of simulating performance in scatternet Bluetooth ad hoc network. AODV, DSR, and DSDV routing protocol also has been implemented on the UCBT Bluetooth module. The result showed that AODV and DSDV protocols are the most suitable routing protocol to be applied in RWP, RDM and RWM.